EVALUASI KEBIJAKAN KURIKULUM TINGKAT SATUAN PENDIDIKAN DI SMA NEGERI 1 AMPIBABO KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Akibu, Rifka S. (Katalogis, 2014)
The objective of this research to figure out result of evaluation of school based curriculumpolicy in SMA Negeri 1 Ampibabo examined based on William Dunn theory using variables such s1) effectiveness, 2) efiiciency, (3 adequateness, 4) equality, 5) responsiveness and 6) accuracy. This was a qualitative research with 5 informants. The research result showed that the implantation of school bsed curriculum in SMA Negeri 1 Ampibabo have not been optimal due to the lack of facilities supporting in the school as the complementary of school Based Curriculum in SMA Negeri1 Ampibabo. The researcher also suggested that the teachers need to understand comprehensively the implementation of school Based Curriculum either in concept, arrangement or the practice in the field.